The effect of marine mineral additions to composite resin on the remineralization process and restoration durability: Pengaruh penambahan mineral laut pada resin komposit terhadap proses remineralisasi dan ketahanan restorasi - Muhammad Ridzki Putra Pratama; Faziah Syardilla Syah; Andi Athalia Savitri; Lenni Indriani (Makassar Dental Journal, 2026)
Composite resin is a widely used restorative material in modern dentistry due to its advantages in aesthetics, mechanical strength, and biocompatibility. How-ever, its clinical performance is challenged by issues such as bond degradation, polymerization shrinkage, and microleakage. Innovations in composite re-sin development have focused on the incorporation of bioactive materials, including marine-derived minerals. Marine minerals such as hydroxyapatite from fish bones, calcium carbonate from shells and corals, and silica from marine diatoms have been explored as fillers or sources of active ions to enhance remi-neralization potential and improve restoration durability. This review aims to examine the current literature on the impact of marine mineral incorporation into composite resins on the remineralization of dental structures and the mechanical performance of restorations. Findings suggest that marine minerals, parti-cularly in nanoparticle form, can enhance calcium and phosphate ion release, promote the repair of demineralized tooth structures, and exhibit antibacterial effects. Nonetheless, further clinical studies are required to support the broader implementation of these materials in dental practice.